Cytomorphological study of palpable benign breast lesions - Naik, Preeta (International Journal of Research in Medical Sciences, 2017)
Background: Benign breast disease is one of the most common lesions of breast in the reproductive age group. Fine needle aspiration cytology (FNAC) is one of the preliminary tests done to detect breast lesions which help in early detection and management. Studying the cytology and histopathology features of various benign breast diseases was the aim of this study. Methods: This study is a cross sectional retrospective study conducted in Department of Pathology during September 2016 to February 2017. Clinical details, cytology and histopathology features were collected from the Department records. Results: A total of 82 cases were collected during the study period. Age groups ranged from 16-40 years. Majority of cases were females and two cases were males. Spectrum of lesions was composed of fibroadenoma, fibrocystic change, breast abscess, benign phyllodes tumor and gynecomastia. Histopathology was done in 41 cases. There was good correlation between cytology and histopathology in this study. Conclusions: Breast lumps are a common cause of anxiety and apprehension among patients. FNAC helps in rapid diagnosis and early management of lesions. It also helps in preventing unnecessary invasive surgeries in non-neoplastic and benign breast diseases.